2013
DOI: 10.1155/2013/459530
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Activity and Redox Profile of the Monoterpenes (+)-Camphene,p-Cymene, and Geranyl Acetate in Experimental Models

Abstract: Objective. To evaluate antinocicpetive and redox properties of the monoterpenes (+)-camphene, p-cymene, and geranyl acetate in in vivo and in vitro experimental models. Methods. Evaluation of the in vitro antioxidant activity of (+)-camphene, p-cymene, and geranyl acetate using different free radical-generating systems and evaluation of antinociceptive actions by acetic acid-induced writhing and formalin-induced nociception tests in mice. Results. p-Cymene has the strongest antinociceptive effect, but (+)-camp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 35 publications
(45 reference statements)
2
61
0
Order By: Relevance
“…), geranyl acetate existing in ylang ylang has an antinociceptive effect (Quintans‐Júnior et al. ), and bornyl acetate contained in conifer leaf oil produces autonomic nerve relaxation (Matsubara et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…), geranyl acetate existing in ylang ylang has an antinociceptive effect (Quintans‐Júnior et al. ), and bornyl acetate contained in conifer leaf oil produces autonomic nerve relaxation (Matsubara et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…p-Cymene has demonstrated only weak antioxidant activity whenever it has been studied and regardless of the assay used (19,23,24). γ-Τerpinene, on the other hand, was found to possess strong antioxidant capacity using the DPPH method (23).…”
Section: Discussionmentioning
confidence: 99%
“…The higher antioxidant activity of samples from the Camas Prairie site for a given amount of polyphenolics could be due to the higher concentration of specific PSMs that have a greater antioxidant activity than others, or it may be due to other classes of PSMs that also have antioxidant capacity that we did not investigate. For example, several monoterpenes, such as (+)-camphene, p -cymene, and borneol, have antioxidant capacity (Kordali et al 2005, Quintans-Júnior et al 2013), and these PSMs are also found in sagebrush (Bray et al 1991, Ulappa et al 2014). …”
Section: Discussionmentioning
confidence: 99%